Mucosal inflammation in Candida esophagitis has distinctive features that may be helpful diagnostically. (November 2018) - Martin, Isabella; Atkinson, Aaron; Liu, Xiaoying; Suriawinata, Arief; Lefferts, Joel; Lisovsky, Mikhail
Abstract The diagnosis ofCandida esophagitis can be challenging when the epithelium containingCandida filamentous forms is not readily seen or is entirely sloughed away. Mucosal inflammation could be helpful diagnostically, if distinctive. However it is thought to be nonspecific inCandida esophagitis. The goal of this retrospective study was to identify features of mucosal inflammation helpful in alerting a pathologist to the possibility ofCandida esophagitis whenCandida mycelia are not readily observed. The study group consisted of 99 consecutive cases ofCandida esophagitis and a control group of 64 consecutive cases of reflux esophagitis diagnosed at our institution from 2008–2016. Band-like superficial intraepithelial neutrophils and increased intraepithelial lymphocytes were observed in 75 and 67% ofCandida esophagitis cases, respectively and only in 14 and 19% of reflux esophagitis cases, respectively (p  < .0001). Intraepithelial lymphocytes were peripapillary or CD4-predominant in 75% ofCandida esophagitis cases with increased lymphocytes, in contrast to 17% of reflux esophagitis cases (p  = .0011). Concurrent presence of intraepithelial neutrophils and increased lymphocytes showed increased specificity forCandida esophagitis and was observed in 61% of patients withCandida esophagitis and only in 2% of patients with reflux esophagitis (p  < .0001). In addition, superficial band-like neutrophils were observed concurrently with increased peripapillary lymphocytes or CD4-predominant lymphocytes in 35 and 50% ofCandida esophagitis cases, respectively, in contrast to no reflux esophagitis cases. Basal cell hyperplasia and elongation of stromal papillae were frequent in both groups. The data suggest that whenCandida microorganisms are not readily observed, concurrent presence of superficial band-like neutrophils and increased lymphocytes may be indicative ofCandida etiology of active esophagitis.